Migratory behaviour does not alter cophylogenetic congruence between avian hosts and their haemosporidian parasites - de Angeli Dutra, Daniela (2022)
Parasites display various degrees of host specificity, reflecting different coevolutionary histories with their hosts. Avian hosts follow multiple migration patterns representing short but also long distances. As parasites infecting migratory birds are subjected to multiple environmental and biotic changes through their flyways, migration may disrupt or strengthen cophylogenetic congruence between hosts and parasites. On the one hand, parasites might adapt to a single migratory host, evolving to cope with the specific challenges associated with the multiple habitats occupied by the host. On the other, as migrants can introduce parasites into new habitats, higher rates of host switching could also disrupt cophylogenetic patterns. We analysed whether migratory behaviour shapes avian haemosporidian parasite-host cophylogenetic congruence by testing if contributions of host-parasite links to overall congruence differ among resident and short-, variable- and long-distance migrants globally and within South America only. On both scales, we found significant overall cophylogenetic congruence by testing whether overall congruence differed between haemosporidian lineages and bird species. However, we found no difference in contribution towards congruence among links involving resident vs migratory hosts in both models. Thus, migratory behaviour neither weakens nor strengthens bird-haemosporidian cophylogenetic congruence, suggesting that other avian host traits are more influential in generating phylogenetic congruence in this host-parasite system.